2020
DOI: 10.1175/mwr-d-19-0308.1
|View full text |Cite
|
Sign up to set email alerts
|

The Hurricane Harvey (2017) Texas Rainstorm: Synoptic Analysis and Sensitivity to Soil Moisture

Abstract: A synoptic analysis and soil moisture (SM) sensitivity experiment is conducted on the record-breaking rainstorm in Texas associated with Hurricane Harvey on 26-30 August 2017. The rainstorm occurred as the moist tropical air mass associated with Harvey was lifted along a frontogenetical near-surface coastal baroclinic zone beneath the equatorward entrance region of an upper-level jet streak. The weak steering winds in Harvey's environment, allowing Harvey to remain nearly stationary, were associated with a def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…According to a study that investigated the effects of various thermal forcings on the development of subtropical anticyclones in the summer, strong land surface sensible heating over each continent generates anticyclones in the upper layers (Liu et al ., 2004). Thus, the dry land condition increases sensible heating that warms and deepens the boundary layer, leading to an anticyclone in the upper atmosphere (850–300 hPa) (Galarneau and Zeng, 2020). Similarly, studies show that a midtropospheric anticyclone is observed in response to dry and hot landmasses (Rácz and Smith, 1999; Kala et al ., 2015; Martius et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study that investigated the effects of various thermal forcings on the development of subtropical anticyclones in the summer, strong land surface sensible heating over each continent generates anticyclones in the upper layers (Liu et al ., 2004). Thus, the dry land condition increases sensible heating that warms and deepens the boundary layer, leading to an anticyclone in the upper atmosphere (850–300 hPa) (Galarneau and Zeng, 2020). Similarly, studies show that a midtropospheric anticyclone is observed in response to dry and hot landmasses (Rácz and Smith, 1999; Kala et al ., 2015; Martius et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The anticyclone and cyclone together resulted in deep-layer northeasterly winds that resulted in deviation of the TC Titli DRY track. In a similar experiment, where initial SM was set to dry for hurricane Harvey (landfall in Texas on August 26, 2017), a combination of anticyclone and cyclone was observed, affecting the course of the cyclone (Galarneau and Zeng, 2020).…”
Section: Impact Of Soil Moisture On Synoptic Featuresmentioning
confidence: 99%
“…Soil moisture plays a key role in the exchange of heat and water between both land and atmosphere and is one of the most studied land surface variables as a source of subseasonal predictability (Seneviratne et al, 2010;Guo et al, 2011;Orth and Seneviratne, 2014;Koster et al, 2017Koster et al, , 2020. Furthermore, soil moisture affects temperature forecasts particularly through its profound memory characteristics, which effectively project dry or wet anomalies into the future (Koster and Suarez, 2001;Orth and Seneviratne, 2012;Galarneau and Zeng, 2020). As a result, they can affect temperature forecast quality in regions with strong land-atmosphere coupling (Koster et al, 2004;Orth, 2021).…”
Section: Relationships Between Temperature Forecast Errors and Earth ...mentioning
confidence: 99%
“…However, the then‐operational models failed to provide a consensus on its track predictions before the first landfall (http://hurricanes.ral.ucar.edu/realtime/plots/northatlantic/2017/al092017/track_early/aal09_2017082518_track_early.png, accessed on 6 November 2022). The unprecedented precipitation and the large track uncertainties around landfall make Harvey a popular research topic (e.g., Galarneau & Zeng, 2020; Ko et al., 2020; P. Wang et al., 2019). Before Harvey's first landfall, four TDR missions were conducted to sample its inner‐core evolution.…”
Section: Introductionmentioning
confidence: 99%